Perspectives on globalisation - Leen, Maura (Statistical and Social Inquiry Society of Ireland, 2002)
The level of public and political debate on the subject of globalisation has grown considerably in recent years. However, as the term enters popular vocabulary, terms such as pro- or anti-globalisation obscure the issues at hand. This paper seeks to engage in a meaningful way with the subject, with particular emphasis on policy advocacy and issues of economic justice. Firstly, the dimensions and interpretations of globalisation are examined. Having provided a framework for analysis, Ireland?s stance on globalisation is investigated from an international development perspective. Finally, the mechanisms for improving global governance are addressed. Challenges and opportunities are identified in an effort to support a type of globalisation which works to reduce exclusion and inequality.
Symposium on Perspectives on Globalisation
Read before the Society, 18 April 2002
Keywords: International development; Global governance; Economic justice; 314.15